Mergers Of Malaysian Domestic Banking Institutions: Causes, Consequences And Implications For The Future - Ling, Chong Siew (2001)
This research evaluate the causes, consequences and implications of Malaysian domestic financial institutions merger in the future. ank Negara Malaysia recognizing the need of merging in the banking sector initiated the merger programme in 1999 where all the domestic bank were given the flexibility to form their own merger groups to 10 banking groups.